Optimizing Cognitive Engagement in Probability Theory: The Integration of Plotagon Animation and PBL-Based Google Sites for Vocational Students - Nurhafizah Hayati; Yulyanti Harisman; Ahmad Fauzan; Suherman (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to develop a mathematics teaching module based on Problem-Based Learning (PBL) supported by Google Sites and Plotagon to enhance vocational high school students’ mathematical problem-solving skills. The research employed a research and development design using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The developed module integrates contextual problems aligned with vocational technology programs and is delivered through an interactive web platform and animated learning videos. Data were collected through expert validation sheets, teacher and student response questionnaires, observation sheets, and problem-solving ability tests. The results showed that the module achieved a high level of validity in terms of content, instructional design, language, and media aspects. The practicality evaluation indicated that the module was easy to use, engaging, and effective in facilitating student learning activities. Furthermore, the effectiveness analysis demonstrated a significant improvement in students’ mathematical problem-solving skills after the implementation of the module. These findings suggest that the integration of PBL with digital platforms such as Google Sites and Plotagon provides an innovative and effective learning environment, particularly for vocational education contexts. Therefore, the developed module is feasible to be implemented as an alternative instructional resource to support mathematics learning and enhance students’ higher-order thinking skills.